1991
DOI: 10.1038/jcbfm.1991.64
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage and Astrocyte Populations in Relation to [3H]PK 11195 Binding in Rat Cerebral Cortex following a Local Ischaemic Lesion

Abstract: PK 11195 is a selective and specific ligand for the peripheral-type benzodiazepine binding site. Its potential for in vivo visualisation of lesioned human brain using positron emission tomography (PET) is currently being assessed. The present study examines the relationship between the temporal development of a local ischaemic lesion with its associated cell populations and the binding of [3H]PK 11195 in rat brain. Unilateral cortical infarcts were induced using the photosensitive dye Rose Bengal. At time inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 28 publications
8
105
0
Order By: Relevance
“…21,27 Indeed, numerous experimental models have shown that autoradiographically detected PK11195 binding correlates better with the temporospatial profile of microglial activation than with that of reactive astrocytes. 18,19,28,29 Discrepancies with other reported cellular localization data using a polyclonal antibody 30 might hint to differences between the sites or PBR subunits recognized by the antibody and those to which (R)-PK11195 binds on tissue sections and in vivo. Cellular localization data from a model of chemically induced demyelination using cuprizone reported by the same group, indicate that in certain lesion-types, astrocytes, too, bind PK11195.…”
Section: Pk11195 Binding To Pbr: From In Vitro Ligand To In Vivo Pet mentioning
confidence: 97%
See 2 more Smart Citations
“…21,27 Indeed, numerous experimental models have shown that autoradiographically detected PK11195 binding correlates better with the temporospatial profile of microglial activation than with that of reactive astrocytes. 18,19,28,29 Discrepancies with other reported cellular localization data using a polyclonal antibody 30 might hint to differences between the sites or PBR subunits recognized by the antibody and those to which (R)-PK11195 binds on tissue sections and in vivo. Cellular localization data from a model of chemically induced demyelination using cuprizone reported by the same group, indicate that in certain lesion-types, astrocytes, too, bind PK11195.…”
Section: Pk11195 Binding To Pbr: From In Vitro Ligand To In Vivo Pet mentioning
confidence: 97%
“…[17][18][19] Early studies of the functional role of the PBR were performed in astrocytes cell cultures, which express high levels of PBR in vitro. 20 As will be discussed shortly, however, these in vitro observations could not be fully extended to the in vivo state.…”
Section: Cellular Source and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, [ 11 C]DAA1106 will be applied for various diseases, and in a case with low k 3 or k 4 , interpretation of the estimated BP would require some caution. The density of PBR was reported to increase in microglia activated by brain damages (Myers et al, 1991;Stephenson et al, 1995;Banati et al, 1997;Kuhlmann and Guilarte, 2000). Cagnin et al (2001) reported that the BP of Alzheimer's disease patients in the [ 11 C]PK11195 study was approximately twice the BP of controls in the inferior and middle temporal gyri, the inferior parietal lobules, and so on.…”
Section: Reliability Of Estimated Parameters With Nonlinear Least-squmentioning
confidence: 99%
“…11195, alongside immunohistochemistry, demonstrated that elevated PBR binding directly correlated with the appearance of activated microglia [26]. More recently, in vivo positron emission tomography (PET) imaging using [ 11 C]PK 11195 in patients suffering from Alzheimer's disease (AD) and multiple sclerosis (MS) It is generally accepted that an increase in PBR density is a reliable marker of microglial activation and neuroinflammation [34] and can therefore be used as an index of active disease in the brain.…”
Section: Introductionmentioning
confidence: 99%